Is the hangul Cervus hanglu hanglu in Kashmir drifting towards extinction? Evidence from 19 years of monitoring - Khursheed Ahmad; Marco Mirelli; Samina Charoo; Parag Nigam; Qamar Qureshi; Rashid Y. Naqash; Stefano Focardi (Oryx, 2023)
The Tarim red deer Cervus hanglu has been recently recognized as a separate deer species with populations in China, Central Asia and Kashmir. These populations are few, isolated and at risk of extinction. The documented range of the Kashmir population of the hangul, now recognized as Cervus hanglu hanglu, is restricted to c. 808 km2 and comprises < 200 individuals, confined mainly to the 141 km2 Dachigam National Park. A few relict herds inhabit the surrounding landscape. Here we analyse the results of almost 20 years of population monitoring (January 2001–March 2020). We found that this population is unable to increase despite full protection within Dachigam National Park. We performed a population viability analysis using both deterministic and stochastic simulations and found that further population decrease is likely. We recommend the use of improved monitoring methods to investigate the population dynamics of the hangul and the implementation of measures to reduce the risk of extinction faced by this small population. Science-based conservation policies, including ex situ conservation and reintroduction programmes, will be required to increase the hangul population size and range.